2008
DOI: 10.1093/ndt/gfn539
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year follow-up of children after acute renal failure from a developing country

Abstract: We found that nearly 25% (n = 6) of the survivors of an acute episode of renal failure had renal morbidity after 10 years, a percentage significant enough for these children to need long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Recent reviews detail the high rates of CKD, hypertension, and microalbuminuria in children who survive an AKI episode (50 ) and reveal a very low rate of long-term follow-up. Children who develop AKI do, in fact, display long-term findings of CKD, as evidenced by the development of hypertension, microalbuminuria, and reduced GFR (Table 2) (37,(51)(52)(53)(54)(55)(56). The post-AKI rates of hypertension, microalbuminuria, and low GFR are remarkable, given the low prevalence of these kidney-related outcomes in the general pediatric population.…”
Section: Aki To Ckd In Childrenmentioning
confidence: 99%
“…Recent reviews detail the high rates of CKD, hypertension, and microalbuminuria in children who survive an AKI episode (50 ) and reveal a very low rate of long-term follow-up. Children who develop AKI do, in fact, display long-term findings of CKD, as evidenced by the development of hypertension, microalbuminuria, and reduced GFR (Table 2) (37,(51)(52)(53)(54)(55)(56). The post-AKI rates of hypertension, microalbuminuria, and low GFR are remarkable, given the low prevalence of these kidney-related outcomes in the general pediatric population.…”
Section: Aki To Ckd In Childrenmentioning
confidence: 99%
“…The investigators found that acute mortality was significantly associated with peak creatinine and the presence of multiple organ failure. Of the survivors, 25% had renal morbidity after 10 years, with at least one of four abnormal renal parameters, including abnormal creatinine, hypertension, hematuria, and proteinuria [63]. Beyond these few studies, there is not much literature on long-term outcome in pediatric AKI.…”
Section: Long-term Prognosismentioning
confidence: 99%
“…Children with AKI experience longer hospitalizations, prolonged intensive care unit (ICU) stays, and greater need for mechanical ventilation (6,9). Additionally, children who survive AKI are likely to experience residual renal abnormalities; proteinuria, hypertension, and reduced GFRs persist in up to 60% of AKI survivors (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%